Nilai-Nilai Pendidikan Islam Dalam Tradisi Penjamasan Pusaka Sunan Kalijaga Pada Masyarakat Kadilangu Demak - Siti Nur Kholifah (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
The tradition of cleansing the Sunan Kalijaga heirloom is considered sacred and is upheld with great reverence by the family. The cleansing process is typically performed only by specific individuals, particularly those of the male lineage. This article aims to discuss the values of Islamic education within the tradition of the Sunan Kalijaga heirloom blessing ceremony among the Kadilangu Demak community. Everyone can apply the values contained in this tradition to their daily lives with sincerity to draw closer to Allah. Field data collection employed a qualitative ethnographic approach. Data collection was conducted using observation and interview techniques and presented through descriptive analysis to describe the phenomena, situations, and conditions occurring during the Sunan Kalijaga heirloom blessing ceremony. The research results indicate that the penjamasan tradition contains Islamic educational values, such as those regarding the relationship between humans and God, humans and the universe, humans and other humans, humans and themselves, as well as faith, exemplary conduct, and moral character.